Microteaching Implementation and Student Readiness for Teaching Practice: A Preliminary Study - TENGKU HAFINDA; Sari Diana; Maya Agustina; Masni (Darul Ilmi Bina Insan Foundation, 2025)
Microteaching plays a crucial role in preparing pre-service teachers, but its implementation is hindered by inconsistent rubrics, the absence of standardized procedures, and concerns about student readiness. This study aimed to explore the implementation of microteaching and student readiness for teaching practice through a preliminary investigation. A descriptive method was employed, combining document analysis and a survey. Document analysis was conducted on three microteaching rubrics used by lecturers and one academic guideline, while the survey involved 20 students who had completed their teaching practice, using five Likert-scale statements. The findings revealed variations in weighting across assessment aspects such as lesson planning, teaching skills, media usage, and reflection. The review also indicated the absence of a specific standardized operational procedure for microteaching. Furthermore, 65% of students reported that microteaching did not adequately prepare them, 55% perceived inconsistency among lecturers’ assessments, and 70% expressed the need for standardized rubrics and a formal microteaching unit. These preliminary results emphasize urgency of conducting a more systematic evaluation of professional practice curricula in teacher education programs.